Drilling bolt holes in finished steel rails (Underwood & Underwood)
View of a worker drilling bolt holes into finished steel rails at an unknown manufacturing plant. This photograph is one of a set of seven stereographs detailing the production of steel.
Keywords: Iron industry and trade; Steel industry and trade; Employees; Manufacturing industries